HMGB1 Activates Myeloid Dendritic Cells by Up-Regulating mTOR Pathway in Systemic Lupus Erythematosus - Song, Xinghui; Zhang, Hui; Zhao, Yun; Lin, Yuanzhen; Tang, Qiya; Zhou, Xiu; Zhong, Xiaoning (Frontiers in Medicine, 2021)
Research has shown that HMGB1 can activate dendritic cells (DCs), but its molecular mechanisms are not clear. In this study, we reported that the myeloid dendritic cells (mDCs) were activated in the peripheral blood of SLE patients, and the activation of mDCs was associated with the up-regulation of HMGB1 and mTOR. After stimulated by HMGB1, expression of mTOR and its substrates P70S6K and 4EBP1 in dendritic cells increased considerably (P < 0.01). The expression of HLA-DR, CD40, and CD86 on dendritic cells also significantly increased following these stimuli (P < 0.01). In addition, stimulation with HMGB1 enhanced cytokine (IL-1β, IL-6, and TNF-a) production in dendritic cells. In contrast, the HMGB1-mediated expression of HLA-DR, CD40, and CD86 on dendritic cells and production of IL-1β, IL-6, and TNF-α were reduced by rapamycin. Rapamycin can inhibit HMGB1-induced activation of mDCs and secretion of pro-inflammatory cytokines. These findings indicated that HMGB1activates mDCs by up-regulating the mTOR pathway in SLE.